(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
India’s educational system has undergone substantial reforms in recent years, driven by the implementation of the National Education Policy (NEP) 2020, which aims to transform the country’s education landscape. This paper explores the key features of the NEP, its impact on Indian education, and the challenges and opportunities arising from these reforms. By analyzing the changes in curriculum structure, pedagogical approaches, and educational governance, this study assesses how these policies are expected to address educational inequities, improve access to quality education, and better prepare students for a rapidly changing world. The paper also provides insights into the future trajectory of educational reforms in India, based on current data and scholarly perspectives from 2023-2025.